Edukasi Tentang Kesadaran Risiko Hipertensi pada Keluarga Berisiko melalui Pendampingan Terapi Modalitas: Slow Deep Breathing, Tanaman Obat Tradisional, dan Pemeriksaan Tekanan Darah Rutin - Popi Sopiah; Reni Nuryani; Nunung Siti Sukaesih; Sri Wulan Lindasari; Tito Chaisar Samuel; Widi Yanti Fadhillah; Annisa Nurul Azizah (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Hypertension is a non-communicable disease that contributes significantly to morbidity and mortality worldwide, including Indonesia. The increasing prevalence of hypertension, particularly in West Java, highlights the importance of preventive efforts through promotive and preventive approaches. This activity aimed to improve the knowledge, attitudes, and skills of families at risk of hypertension in self-management through therapeutic modality assistance, including Slow Deep Breathing, traditional medicinal plants, and routine blood pressure monitoring. The method involved health education using lectures, demonstrations of Slow Deep Breathing techniques, and education on the utilization of herbal plants such as turmeric and ginger. A total of 37 participants with hypertension participated in health assessments, pre-tests, educational sessions, and practical activities. Evaluation was conducted through educational booklets and monthly blood pressure monitoring for three months. The results showed that most participants had uncontrolled blood pressure (≥140/90 mmHg) and inadequate self-care behaviors based on the H-SCALE instrument. After the intervention, participants demonstrated improved knowledge, awareness, and skills in hypertension management, as well as increased motivation to practice therapeutic modalities. This approach can be implemented sustainably in the community to support hypertension prevention and reduce the risk of complications.